Factors associated with leakage in patients with an ostomy: A cross‐sectional study - Kirsten Lerum Indrebø; Anny Aasprang; Torill Elin Olsen; John Roger Andersen (Wiley, 2023)
Abstract Aims To explore the associations between sociodemographic and clinical data, the patient's knowledge and skills, and relationship to healthcare professionals with leakage from an ostomy. Design Cross‐sectional. Methods This study included 160 patients with a colostomy, ileostomy, or urostomy. Leakage was the dependent variable and was assessed by self‐report. Sociodemographic and clinical data and the Ostomy Adjustment Scale subscores, 'knowledge and skills' and 'health care professionals' were independent variables. Spearman's rho and multivariate partial least squares regression analysis were used to estimate possible factors associated with leakage. Results Of the participants, 13.8% had leakage weekly or more often, 16.3% more often than once a month and 37, 5% had leakage more seldom than once a month. The most important risk factors for leakage were (1) having an ostomy placement that does not meet international guidelines, (2) not having an optimal relationship with health professionals, (3) having a diagnosis other than cancer, (4) not having proper knowledge and skills in ostomy care, (5) not having a colostomy, (6) having a convex baseplate, (7) having an oval ostomy, and (8) being dependent on others for ostomy care. The independent variables in the PLS‐ model explained 31% of the variance in leakage. Patient or Public Contribution We thank the patients in the user panel for their help during the study.